The Impact of Leadership, Motivation, and Remuneration on Employee and Organizational Performance at PTN-BH in Sumatra - Radhi, Fahrul; Yunus, Mukhlis; Amiruddin, Amiruddin; Ruslan, Ruslan; Kesuma, T Meldi; Alexandri, Mohammad Benny (SCAD Independent, 2025)
In recent years, Indonesian universities have transitioned to legal entity state universities (PTN-BH). This transition significantly impacts employee performance, requiring adjustments in organizational management, particularly in leadership, motivation, and remuneration. This study investigated how leadership style, motivation, and employee compensation influence civil servant performance and, in turn, the performance of PTN-BH universities in Sumatra. The research focused on Universitas Sumatera Utara (USU), Universitas Andalas (UNAND), Universitas Negeri Padang (UNP), and Universitas Syiah Kuala (USK), with a population of 4,382 teaching staff members who have at least five years of service. A sample of 367 individuals was selected using the Slovin formula. Data analysis was conducted using Structural Equation Modeling (SEM) with SPSS-AMOS-22 software. Key findings showed that leadership style, motivation, and remuneration directly impact both employee and organizational performance. Specifically, leadership style affected both employee and organizational performance, as do motivation and remuneration. Employee performance served as a partial mediator between leadership style and organizational performance, as well as between motivation and organizational performance. The study highlighted how improving leadership practices, motivating employees effectively, and ensuring fair compensation contribute to the overall success of Legal Entity State Universities in Sumatra.